Electrochemical characterization of hydroxylated xanthones by cyclic voltammetry - Santos, Clementina M.M. (2012)
Xanthones constitute a class of oxygenated heterocyclic compounds commonly identified in some higher plant families, fungi and lichens [1]. Their large variety of biological and pharmacological activities encouraged the scientific community for the search and isolation of natural derivatives for therapeutic applications [2]. Consequently, extensive studies have been devoted to the development of synthetic routes for the preparation of these naturally-occurring compounds or other synthetic bioactive derivatives [3,4]. For the present study, xanthones XH1-9 were obtained by synthesis and the diversity of substitution pattern includes the presence of phenolic and catecholic moieties. These structural features are important requisites for the scavenging activity against reactive oxygen and nitrogen species already demonstrated by these molecules [5]. During the last decades, electrochemical studies have been widely used for the evaluation of structure-antioxidant activity relationship of several phenolic compounds [6,7]. Thus, the electrochemical profile of xanthones XH1-9 can provide useful information about their electrochemical reactions, which may be used to predict or explain their biological properties. In this communication we will report the electrochemical characterization by cyclic voltammetry of various hydroxylated xanthones, in physiological conditions. The oxidation potential value versus structure relationship will be highlighted and some considerations about the oxidation mechanism will be presented.